Farmer Community Emowerment in Indonesia - Noventi, Ike Arni (Jurnal Ilmiah Administrasi Publik, 2017)
Food sufficiency is closely related to a country’s political stability. In order to achieve food sufficiency, local government need to conduct agriculture development which more focus on farmer community empowerment as main actor of ariculture development. This research aims to describe the efforts of local governmnet in empowering farmer community and analyze the appropriateness of those efforts with community empowerment concept. Descriptive research method with qualitative approach is used in this research. The result shows that local government has conducted farmer community empowerment efforts through several activities which are appropriate with the concept of community empowerment such as training, counseling, forming network, socialiszation, and providing loan. However, local government also gives subsidies and grant which are contrary to the concept of community empowerment and have potential to increase the dependence of the farmer on the local government.